Effect of Loan to Deposit Ratio (LDR) and Non-Performing Loans (NPL) on Return on Assets (ROA) - Tresnawati, Rina (International Journal of Psychosocial Rehabilitation, 2020)
Banking is one of the financial institutions that has the main activity of raising funds from the community and channeling these funds in the form of loans to the community. Loan to Deposit Ratio (LDR), Non-Performing Loans (NPL), and Return on Assets (ROA) are bank financial ratios used to assess banking performance. The ratio of loans to deposits (LDR) and non-performing loans (NPL) to the return on assets (ROA) case study at PT. Mitra Mitra Kanaka Santosa financial statements for the period 2013-2017. The research methodology used is multiple regression linear analysis, which obtained partial results that the ratio of Loan to Deposit Ratio (LDR) has a significant positive effect on Return on Assets (ROA), Non-Performing Loans (NPL) has a significant positive effect on Return on Assets (ROA), and simultaneously obtained a significant Loan to Deposit Ratio (LDR) and Non-Performing Loan (NPL) to Return on Assets (ROA).